Germline Profiling and Molecular Characterization of Early Onset Metastatic Colorectal Cancer - Xu, Ting; Zhang, Yinjie; Zhang, Jing; Qi, Changsong; Liu, Dan; Wang, Zhenghang; Li, Yanyan; Ji, Congcong; Li, Jian; Lin, Xuan; Hou, Ting; Liu, Hao; et al. (Frontiers in Oncology, 2020)
Background Early onset colorectal cancer (EOCRC) is a heterogeneous colorectal cancer subtype with obvious hereditary tendencies and increasing incidence. We sought to determine the susceptibility genes and molecular characteristics of EOCRC. Methods 330 EO metastatic CRC (mCRC) (≤55 years) and 110 average-onset (AO) mCRC patients (>55 years) were enrolled. Capture-based targeted sequencing was performed on tumor tissue and paired white blood cells using a sequencing panel of 520 genes. The association between molecular alterations and overall survival (OS) was analyzed. Results Of the 330 EO mCRC patients, 31 carried pathogenic or likely pathogenic germline mutations, with 16 of them diagnosed with lynch syndrome. Fifteen patients had germline mutations in non-mismatch repair genes, including 4 in MUTHY, 3 in RAD50, 1 in TP53, and 8 in other genes. Twenty-nine genes were recurrently mutated in EO mCRC, including TP53, APC, KRAS, SMAD4, and BRCA2. The majority of genomic alterations were comparable between EO and AO mCRC. EO mCRC were more likely to have a high tumor mutation burden (p < 0.05). RNF43, RBM10, TSC, and BRAF V600E mutations were more commonly observed in EO mCRC, while APC, ASXL1, DNMT3B, and MET genes were more commonly altered in AO patients. At the pathway level, the WNT pathway was the only differentially mutated pathway between EO and AO mCRC (p < 0.0001). The wild-type WNT pathway (p = 0.0017) and mutated TGF-β pathway (p = 0.023) were associated with unfavorable OS in EO mCRC. Conclusions Approximately 1 in 10 EO mCRC were associated with hereditary tumors. The spectrum of somatic alterations was largely comparable between EO and AO mCRC with several notable differences.